2016
DOI: 10.1039/c5ra24328a
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and kinetic studies on MB adsorption by ultrathin 2D MoS2nanosheets

Abstract: MoS2 ultrathin nanosheets display excellent adsorption ability towards methylene blue, with a maximum adsorption capacity of 146.43 mg g−1 in 300 seconds. Moreover, the adsorbent can be resued by washing with deionized water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(80 citation statements)
references
References 41 publications
4
76
0
Order By: Relevance
“…21 The two-dimensional MoS 2 nanosheets showed potential as an efficient adsorbent for removal of methylene blue (MB) dye following the pseudo-second order adsorption kinetics. 22 The MoS 2 nanosheets decorated with magnetite Fe 3 O 4 nanoparticles exhibited good adsorption capacity for the Congo red and can be quickly separated from the suspension owing to their magnetic properties. 23 In this paper, we report one-step approach to synthesize the hierarchical microspheres of MoS 2 nanosheets and then demonstrated as highly efficient adsorbent for organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…21 The two-dimensional MoS 2 nanosheets showed potential as an efficient adsorbent for removal of methylene blue (MB) dye following the pseudo-second order adsorption kinetics. 22 The MoS 2 nanosheets decorated with magnetite Fe 3 O 4 nanoparticles exhibited good adsorption capacity for the Congo red and can be quickly separated from the suspension owing to their magnetic properties. 23 In this paper, we report one-step approach to synthesize the hierarchical microspheres of MoS 2 nanosheets and then demonstrated as highly efficient adsorbent for organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several reports claimed fast and efficient adsorption of different organic dyes using MoS 2 composites. [1][2][3][4]6,[21][22][23][24][25][26][27][28] He Li et al 29 used porous MoS 2 nanosheets to efficiently remove RhB, MB and MO with adsorption capacities of about 163.0 mg g À1 , 499.0 mg g À1 and 125.1 mg g À1 at 420 min, respectively. Also, Xiu and co-workers 21 found that the MoS 2 exhibits good and fast performance for removal of MB from aqueous solution, with an adsorption capacity of 146.43 mg g À1 in 6 min.…”
Section: Introductionmentioning
confidence: 99%
“…3) passing through the origin. A case opposite to the above, indicates different mass transfer rates in the initial and final stages of adsorption, indicating the involvement of film diffusion in addition to intra particle diffusion [33,34]. Figure 10d shows the linear fitting plot of intra particle diffusion model.…”
Section: Photocatalytic Experiments and Kinetic Analysismentioning
confidence: 92%